Comparative Study of Mathematics Education in Indonesia, Singapore and England (United Kingdom) - Guntur, Muhamad Ikhsan Sahal; Maharani, Fitria (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
This comparative study of mathematics education in Indonesia, Singapore and England aims to analyze the differences and similarities in three main aspects, namely the mathematics learning curriculum, evaluation system and teacher recruitment. This research examines how mathematics curricula in these three countries are structured to meet the educational needs of the 21st century, with a focus on developing critical thinking and problem-solving skills. In Indonesia, the mathematics curriculum is often more oriented towards achieving national standards, whereas in Singapore and the UK, the curriculum tends to be more flexible and based on holistic development of student competencies. In terms of the evaluation system, Indonesia relies on national exams and standards-based tests, while Singapore and the UK use a more diverse approach, including competency-based evaluations and formative assessments. Finally, in terms of teacher recruitment, Indonesia still faces challenges in ensuring the quality and number of teaching staff meet standards, while Singapore and the UK have strict selection systems and focus on developing teacher professionalism through continuous training. It is hoped that the results of this study will provide insight into the development of mathematics education policy in Indonesia, as well as enrich understanding of best practices applied in other countries.